2019
DOI: 10.1111/jors.12433
|View full text |Cite
|
Sign up to set email alerts
|

The effect of culture on home‐ownership

Abstract: In this paper, we analyze the role of culture in determining whether, or not, an individual is a homeowner. We use data on first-generation immigrants who arrived in the United States under six years old. Following the epidemiological approach, any dissimilarity in the proportion of homeowners by country of origin may be interpreted as a consequence of cultural differences. Our estimates indicate that there is a positive and statistically significant relationship between the cultural proxy and the immigrants' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Cultural norms significantly mold property preferences, shaping housing choices and community living, providing crucial socio-cultural insights (Marcén & Morales. 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cultural norms significantly mold property preferences, shaping housing choices and community living, providing crucial socio-cultural insights (Marcén & Morales. 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under different cultural backgrounds, residents’ family concepts and intergenerational relationships vary widely, and their housing consumption preferences will also change accordingly, which will lead to differences in their housing tenure choice. In terms of research on culture on homeownership choices, Marcén and Morales (2020) analyzed the role of culture in determining whether an individual is a homeowner using data from first-generation immigrants arriving in the United States under the age of 6, suggesting that culture is a homeownership decision important factors. Cultural differences and policy biases affect housing rental and purchase choices ( Tabner, 2016 ).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Therefore, it seems critical to consider other factors that influence homeownership choices. Some studies have shown that culture is an important factor influencing consumers’ housing consumption decisions ( Marcén and Morales, 2020 ). Particularly in the Chinese cultural context, housing consumption behavior is not only a commodity-rich behavior, but it is also a socio-culturally distinct behavior.…”
Section: Introductionmentioning
confidence: 99%
“…E.g. Marcén and Morales [ 7 ] found out that culture understood as a set of different values, beliefs, traditions etc. is a significant factor in home-ownership.…”
Section: Introductionmentioning
confidence: 99%